Evaluating the relevance and clarity of the heart failure eMeasure implementation toolkit by using a webbased survey instrument - Megha Kalsy; Katherine Sward; Bruce Bray; Andrew Redd; Karen Eilbeck; Jennifer H Garvin (Annals of Circulation - Peertechz Publications, 2019)
Background: The impact on workfl ow is an important component in determining whether an HIT implementation will be successful. Workfl ow is, unfortunately, a concept that is often ignored when implementing HIT and the literature about workfl ow in domains of quality improvement, system implementation, and process improvement has not been adequate. HIT is not always designed to fi t the workfl ow of a given organization, making it diffi cult to truly assess HIT impact on outcomes or processes.